The Relationship between Managerial Skills and Teaching Effectiveness of Elementary School Teachers - Mercedita H. Silva (International Journal of Educational Management and Development Studies, 2021)
This study aimed to find out any significant relationship between the managerial skills and teaching effectiveness of the selected elementary teachers. Using a descriptive method of research, a total of 62 public elementary teachers from eleven (11) elementary schools in Candelaria West District in the Philippines during the academic year 2018-2019 were chosen as study participants. An expert-validate questionnaire in checklist form was the main tool for data collection. The perceived managerial skills of the teachers were manifested through their technical, conceptual and human skills. Meanwhile, the level of the teaching effectiveness is always effective in terms of management of students’ behavior and assessment of students’ learning and effective in organization of instruction and adjustment of learning. Results further revealed that there was significant relationship in managerial skills and teaching effectiveness in terms of management of students’ behavior, organization of instruction, assessment of students’ learning and adjustment of learning. The managerial technical skill was significantly related to teaching effectiveness. There is perceived necessity to develop further the managerial skills of the teachers. Administrator may provide programs and activities for improvement and application of teachers’ managerial skills.